A Configurable Interface Unit for Telemetry Monitoring in Satellites - Hagslätt, Fredrik; Johansson, Fredrik (My University, 2018)
This report presents a concept for a flexible remote interface unit for telemetry monitoring in satellites. The concept consists of a flexible hardware interface that can be configured by a microcontroller into reading several different types of sensors. An important aspect in the introduced flexibility is the presented method for filtering signals digitally, eliminating the need for slow analog low-pass filters. The feasibility of the concept is verified and its expected performance is evaluated. The performance evaluation is based on acquisition times that are affected by the hardware’s configuration time, the sensor’s settling times and the time needed for digital filtering. The report also summarizes the number and types of sensors on several finished satellites to evaluate how many the proposed concept can cover. Digital filtering together with the evaluation of performance and coverage shows that this concept can be further developed into a flexible design that can cover future projects without the need for major hardware changes, thus reducing development costs.
Keywords: Informations- och kommunikationsteknik; Data- och informationsvetenskap; Information & Communication Technology; Computer and Information Science